2020
DOI: 10.3390/su12093553
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking Using Project-Based Learning: The Case of The Agroecological Market at the “Universitat Politècnica de València”

Abstract: Higher education institutions play an important role in the transition processes to sustainable development through developing critical thinking (CT) in their students. The case of the Research Methodology course of the International Cooperation Master’s degree at the Universitat Politècnica de València is a paradigmatic case of experiential learning, where students face their own realities related to sustainable topics through an action research project with the Agroecological Market (AM). The learning method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 54 publications
3
9
0
1
Order By: Relevance
“…The significant difference was at 0.01 level. These findings are consistent with many other studies that revealed significant impact for project based learning whether face to face or online on critical thinking skills such as (Aránguiz et al, 2020), (Alawi & Soh, 2019;Eldiva & Azizah, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…The significant difference was at 0.01 level. These findings are consistent with many other studies that revealed significant impact for project based learning whether face to face or online on critical thinking skills such as (Aránguiz et al, 2020), (Alawi & Soh, 2019;Eldiva & Azizah, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Project-based learning involves real-life challenges, focusing on authentic questions, and the solutions in real life. The research findings are in line with Project-based learning is an innovative learning model or approach, which emphasizes contextual learning through complex activities (Aránguiz et al, 2020). the PjBL learning model has seven characteristics as follows involving students directly in learning, connecting learning with the real world, implementing on a research-based, involving various research sources, combining with knowledge and skills, carried out from time to time, and ended with a certain product (Abidin, 2014;Abidin et al, 2017).…”
Section: Learning Activitysupporting
confidence: 78%
“…Therefore, developing critical thinking skills can be done through learning practices in lectures using various methods, strategies, and learning models determined by the lecturer, and one of which is by using the project-based learning model. The use of project-based learning model based on personal or real experience can help students reflect on their critical thinking by analyzing in-depth the problems that exist and can be found in everyday life; thus, the provision of good critical thinking skills will be beneficial (Aranguiz et al, 2020). Therefore, the researcher wants to conduct a study on applying the project-based learning model in the Social Sciences 1 course, PGSD FKIP study program, University of P. It is assumed that is a learning model using activities or projects to provide an understanding of one material.…”
Section: Introductionmentioning
confidence: 99%